The Influence of Female Leadership, Work Discipline, and Work Motivation Using Work Environment as an Intervening Variable on the Performance of Elementary School Teachers in West Bontang District - Ariyanti, Yeni; Mulawarman, Widyatmike Gede; Azainil, Azainil; Halimah, Siti; Fitriadi, Ahmad; Tumanan, Siska (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2024)
Abstract: This study aims to analyze the influence of female leadership, work discipline, and work motivation on teacher performance, using the work environment as an intervening variable in primary schools in the West Bontang District, Bontang City. Teacher performance is a key factor in improving the quality of education in schools, which is influenced by various factors, including the work environment. This research uses a quantitative approach with a survey method. The study sample consists of primary school teachers in the West Bontang District, selected through proportionate random sampling techniques. Data collection was conducted using a questionnaire that was tested for validity and reliability. Data analysis was performed using the SEM-PLS model to examine the relationships between variables. The results of the study show that female leadership does not have a significant influence on teacher performance. Work discipline also does not have a significant impact on teacher performance. However, work motivation has a positive and significant effect on teacher performance. The work environment was found to play a significant role as an intervening variable in mediating the relationship between work motivation and teacher performance. Work motivation and the work environment play important roles in improving teacher performance, while female leadership and work discipline do not have a significant impact. This study suggests that schools should enhance motivation and create a conducive work environment to better support teacher performance. Keywords: Female Leadership, Work Discipline, Work Motivation, Work Environment, Teachers Performance